New taxa of Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from Guangxi, China - Wang, Hanqiang; Liu, Xianwei; Li, Kai (Zootaxa, 2015)
The following new taxa of Meconematini from Guangxi province were described: Sinothaumaspis damingshanicus Wang, Liu, Li gen. & sp. nov., Aphlugiolopsis punctipennis Wang, Liu, Li gen. & sp. nov., Eoxizicus (Eoxizicus) curvicercus Wang, Liu, Li sp. nov., Meconemopsis paraquadrinotata Wang, Liu, Li sp. nov., Neocrytopsis? unicolor Wang, Liu, Li sp. nov., Xiphidiopsis (Dinoxiphidiopsis) expressa Wang, Liu, Li sp. nov. Xiphidiopsis (Xiphidiopsis) fischerwaldheimi Gorochov, 1993, a synonym of Xiphidiopsis (Xiphidiopsis) jinxiuensis Xia & Liu, 1990 was described. The opposite gender of Sinocyrtaspis truncate Liu, 2000 and Abaxinicephora excellens Gorochov & Kang, 2005 were firstly described. Xiphidiopsis (Dinoxiphidiopsis) jacobsoni Gorochov, 1993 was also firstly recorded from China. Two new combinations, Meconemopsis quadrinotata (Bey-Bienko, 1971) Wang, Liu, Li comb. nov. and Xiphidiopsis (Dinoxiphidiopsis) fanjingshanensis (Shi & Du, 2006) Wang, Liu, Li comb. nov., as well as a synonym of the former Xizicus (Axizicus) xizangensis Jiao & Shi 2013 syn. nov. which respectively relate to M. paraquadrinotata sp. nov. and X. (D.) expressa sp. nov., were also noted.